International Cooperation Relations and Supply Chain of the Republic of Korea in the Conditions of the Global Economic Crisis - R Nurieva; M.Z Gibadullin; Ko Young Cheol; I.T Nasretdinov (International Journal of Supply Chain Management, 2020)
Abstract- This prime aim of this study is to investigate the relationship between imports, exports, supply chain management and international relations along with mediation effect of import export policies. The Republic of Korea is one of the states whose participation in the system of international economic relations remains noticeable, despite the unfavorable background of external factors. The article sets the task of determining the sustainability of international cooperation relations of the Republic of Korea in the conditions of the global economic crisis.